2021
DOI: 10.1093/icvts/ivab087
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical circulatory support in coronavirus disease-2019-positive patients with severe respiratory failure

Abstract: OBJECTIVES Treatment of severe acute respiratory distress syndrome (ARDS) induced by severe acute respiratory syndrome coronavirus 2 has been heavily debated. Our goal was to describe our findings in patients with severe ARDS due to severe coronavirus disease 2019 (sCOVID-19) treated with venovenous extracorporeal membrane oxygenation (vv-ECMO). METHODS We retrospectively examined all patients treated with vv-ECMO for severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…However, due to a relatively small number of patients, we could not establish significant results. 18 In this study, we were able to provide proof that vv-ECMO implantation <48 h after admission was associated with improved survival. To our knowledge, this is the first time that a clear correlation between the time of vv-ECMO implantation and survival has been described.…”
Section: Discussionmentioning
confidence: 61%
“…However, due to a relatively small number of patients, we could not establish significant results. 18 In this study, we were able to provide proof that vv-ECMO implantation <48 h after admission was associated with improved survival. To our knowledge, this is the first time that a clear correlation between the time of vv-ECMO implantation and survival has been described.…”
Section: Discussionmentioning
confidence: 61%
“…There were 18 studies reporting the events of major bleeding in COVID-19 patients who received ECMO support, 19,20,22,2729,3739,43,46,49,50,52,5658,60 and the incidence of hemorrhage varied from 3.7% to 81.3%. Meta-analysis of proportions found that the pooled incidence rate of bleeding requiring transfusion was 39% (95% CI 28%–52%, I 2 = 76%; Figure 4) in ECMO-assisted patients with COVID-19.
Figure 4.Forest plot of the incidence of bleeding requiring transfusion in COVID-19 patients treated with ECMO.
…”
Section: Resultsmentioning
confidence: 99%
“…Total 27 studies including 1103 patients with COVID-19 who developed ARDS reported inhospital mortality. [21][22][23][25][26][27][28][29][31][32][33]35,36,39,41,42,[44][45][46][47][48][49][50]52,56,59,60 It varied from 3.7% to 65.6% in an overall hospital setting. Meta-analysis of proportions revealed the pooled incidence rate of in-hospital death was 35% (95% CI 30%-42%, I 2 = 72%; Figure 3) in all hospitalized patients.…”
Section: Primary Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…Extracorporeal membrane oxygenation (ECMO) is an effective means of treating critically ill cardiopulmonary dysfunction. ECMO has attracted much attention [ 1 , 2 , 3 , 4 , 5 ], as the coronavirus disease 2019 (COVID-19) continues to ravage the world since the use of ECMO is clinically beneficial for patients with severe heart failure or lung failure [ 6 , 7 , 8 , 9 ]. One of the key parts of ECMO comprises hollow fiber oxygenation membranes, which are made from polyolefin, e.g., polydimethylsiloxane, poly-1-methyl-4-pentene, polypropylene, and other polyolefin polymers [ 10 ], and polypropylene (PP) is one of the promising membrane material due to its stable, inexpensive, and easy-to-process characteristics.…”
Section: Introductionmentioning
confidence: 99%